Analysis of Organizational Culture and Leadership Style in Improving Employee Performance at Yayasan Aksi Indonesia Dermawan - Noviyanti, Widya (Universitas Pamulang, 2025)
Human resources (HR) serve as a strategic factor in the success of an organization, including Yayasan Aksi Indonesia Dermawan. Employee performance is influenced by various factors, particularly leadership style and organizational culture. An effective leadership style can enhance employee motivation and engagement in achieving organizational goals. Additionally, a strong organizational culture establishes values and norms that support productivity and teamwork. This study aims to analyze the impact of leadership style and organizational culture on employee performance at Yayasan Aksi Indonesia Dermawan. Employing a descriptive qualitative approach, this research examines the internal organizational dynamics and the factors contributing to employee performance. The findings indicate that the participative leadership style implemented within the foundation positively influences employee motivation. However, challenges remain in communication and transparency. Furthermore, a collaboration- and innovation-oriented organizational culture contributes to performance improvement, although further reinforcement is needed in recognizing individual achievements. In conclusion, effective leadership and a strong organizational culture play a crucial role in enhancing employee performance at Yayasan Aksi Indonesia Dermawan. Therefore, improved strategies for internal communication and reward systems are necessary to maximize the potential of existing human resources.